Rethinking liquid biopsy: Microfluidic assays for mobile tumor cells in human body fluids. (January 2018) - Neoh, Kuang Hong; Hassan, Ayon Ahmed; Chen, Anqi; Sun, Yukun; Liu, Peng; Xu, Kai-Feng; Wong, Alice S.T.; Han, Ray P.S.
Abstract: Traditionally, liquid biopsy is a blood test involving the harvesting of tumor materials from peripheral blood. Tumor cells from non-blood body fluids have always been clinically available in cytological examinations but limited for use in differential diagnosis due to the low sensitivity of conventional cytopathology. With the recent significant progress in microfluidic and downstream molecular technologies, liquid biopsies have now evolved to include harvesting tumor cells and DNA fragments in all kinds of non-blood body fluids. This expansion into general body fluids presages the notion that liquid biopsy could soon be used in competition, as well as, in complementarity with tissue biopsy. Preliminary research of fluid-harvested tumor materials to spot early-stage tumors, monitor disease progression for metastasis and recurrence, and detect chemoresistance have been reported. To reflect the propagation of tumor cells in non-blood body fluids, we introduced the term Mobile Tumor Cells (MTCs), in lieu of the widely accepted term of circulating tumor cells (CTCs) resident in the bloodstream. Our review starts with a discussion on the clinical significance of MTCs, followed by a presentation of microfluidic techniques for MTC capture and various strategies for their identification. Hopefully, the phenotypic and genomic data acquired from harvested MTCs can be used to guide and improve cancer treatment decisions.